Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja ASN Satuan Polisi Pamong Praja (Satpol-PP) Sumatera Selatan - Patrio Zona Putra; Heriyanto Heriyanto (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims: (1) to determine the effect of work motivation on the performance of ASN Satpol PP South Sumatra (2) to determine the effect of work discipline on ASN performance (3) to determine the effect of work motivation and work discipline together (simultaneously) on performance. The sample in this study was 51 respondents who were Asn Satpol-Pp South Sumatra, the sampling method used by the researcher was the Purposive Cluster random sampling method. This type of research is quantitative research using multiple regression analysis techniques, classical assumption test, validity and reliability testing, hypothesis testing through t test and f test, as well as correlation coefficient analysis and determination,From the results of this study, the effect of work motivation partially has no significant effect on the performance of ASN SATPOL-PP SUMSEL this can be seen from the T test, namely tcount of -0.234 < ttable 2.010 with a significance of 0.816> 0.05. Work discipline partially has a significant effect on ASN performance, this can be seen from the T test, namely tcount of 20.208 > ttable of 2.010 with a significance of 0.00 <0.05. It can be concluded that there is a significant positive effect of work discipline on the performance of ASN, the variable of work motivation and work discipline has a significant effect simultaneously (simultaneously) on the performance dependent variable with a value of fcount 339.8 > ftable 3.19 with a significance value of 0, 00 < 0.05. Based on the coefficient of determination R square (R) of 0.934 or 93.4%, it means that the contribution of work motivation (X1) and work discipline (X2) to (Y) is 93.4% and the rest (100% -93.4 %) 6.6% influenced by other factors.